Hemoglobin and Erythropoietin After Commercial Saturation Diving - Kiboub, Fatima Z.; Balestra, Costantino; Loennechen, Øyvind; Eftedal, Ingrid (Frontiers in Physiology, 2018)
Saturation divers are exposed to elevated partial pressure of oxygen (ppO2) in their hyperbaric work environment. Experimental studies indicate that oxygen transport is altered, and we have previously reported a drop in hematocrit and extensive downregulation of genes involved in blood oxygen transport capacity after decompression from professional saturation diving.Here we investigate the initial period of hematological adjustment back to normobaric air after professional saturation diving. Erythropoietin (EPO) and hemoglobin (Hb) were measured in blood from 13 divers at two time-points after saturation assignments lasting up to 4 weeks; first immediately after decompression and again 24 h later. Pre-dive levels defined baselines. The ppO2 varied from 40 kPa in the saturation chambers during storage, 50 to 80 kPa during bell excursions, and gradually reduced to 21 kPa during decompression to surface pressure. EPO was similar to baseline immediately after saturation diving (P = 0.4), and markedly increased within the next 24 h (99%, P < 0.0002). Hb levels remained slightly reduced at both time-points (4% immediately after; P = 0.02, 8% 24 h after; P < 0.001). The results imply that the hematological acclimatization back to normobaric air was ongoing, but not completed, during the first 24 h after professional saturation diving.